Transgene and Chemical Transdifferentiation of Somatic Cells for Rapid and Efficient Neurological Disease Cell Models - Ng, Neville; Newbery, Michelle; Maksour, Simon; Dottori, Mirella; Sluyter, Ronald; Ooi, Lezanne (Frontiers in Cellular Neuroscience, 2022)
For neurological diseases, molecular and cellular research relies on the use of model systems to investigate disease processes and test potential therapeutics. The last decade has witnessed an increase in the number of studies using induced pluripotent stem cells to generate disease relevant cell types from patients. The reprogramming process permits the generation of a large number of cells but is potentially disadvantaged by introducing variability in clonal lines and the removal of phenotypes of aging, which are critical to understand neurodegenerative diseases. An under-utilised approach to disease modelling involves the transdifferentiation of aged cells from patients, such as fibroblasts or blood cells, into various neural cell types. In this review we discuss techniques used for rapid and efficient direct conversion to neural cell types. We examine the limitations and future perspectives of this rapidly advancing field that could improve neurological disease modelling and drug discovery.